EVALUASI PEMENUHAN INDIKATOR STANDAR PELAYANAN MINIMAL JALAN TOL DI INDONESIA - Makmur, Amelia; Rajagukguk, Ranto P. (Jurnal Transportasi, 2015)
Abstract The Minimum Service Standard for toll road services is needed to ensure the achievement of comfort, smoothness, and traffic safety for road users. The Minimum Service Standard that applies to all toll roads in Indonesia is the Minimum Service Standard, which refers to the Regulation of the Minister of Public Works No. 392/PRT/M/2005 on Minimum Service Standards for Toll Road. Monitoring and evaluation of the fulfillment of the Minimum Service Standard has been done periodically, but there are still some indicators that cannot always be met by Toll Road Operators. This study is intended to assess the indicators which cannot always be met in the toll road sections that have been operating in Indonesia. The study was conducted based on monitoring data, the result of field survey, conducted in 27 toll roads in 2012, 2013, and 2014. Based on the analysis, it is found that there are 6 indicators of the Minimum Service Standard that often cannot be met, or 29 % of the indicators in the Minimum Service Standard. Keywords: Minimum Service Standard, toll road service, toll road, service indicator Abstrak Standar Pelayanan Minimal untuk pelayanan jalan tol sangat diperlukan untuk menjamin tercapainya kenyamanan, kelancaran, dan keselamatan berlalulintas bagi pengguna jalan. Standar Pelayanan Minimal yang berlaku untuk seluruh jalan tol di Indonesia adalah Standar Pelayanan Minimal yang mengacu kepada Peraturan Menteri Pekerjaan Umum Nomor 392/PRT/M/2005, tentang Standar Pelayanan Minimal Jalan Tol. Monitoring dan evaluasi terhadap pemenuhan Standar Pelayanan Minimal ini sudah dilakukan secara berkala, namun masih banyak ditemukan beberapa indikator pelayanan yang selalu tidak dapat dipenuhi oleh Badan Usaha Jalan Tol. Studi ini dimaksudkan untuk mengkaji indikator-indikator yang selalu tidak dapat dipenuhi di ruas-ruas jalan tol yang telah beroperasi di Indonesia. Kajian dilakukan berdasarkan data monitoring, hasil survei lapangan, yang dilakukan pada 27 ruas jalan tol pada tahun 2012, tahun 2013, dan tahun 2014. Berdasarkan analisis yang dilakukan ditemukan 6 indikator Standar Pelayanan Minimal yang selalu tidak dapat dipenuhi atau sebesar 29 % dari indikator-indikator yang terdapat dalam Standar Pelayanan Minimal. Kata-kata kunci: Standar Pelayanan Minimal, pelayanan jalan tol, jalan tol, indikator pelayanan.